Enhanced Energy Storage of Dielectric Nanocomposites at Elevated Temperatures. Issue 1 (23rd May 2015) - Rajib, Mohammad; Martinez, Ricardo; Shuvo, Mohammad; Karim, Hasanul; Delfin, Diego; Afrin, Samia; Rodriguez, Gerardo; Chintalapalle, Ramana; Lin, Yirong
Abstract : Enhancing the performance of dielectric capacitors toward higher energy density and higher operating temperatures has been drawing increased interest. Therefore, in this investigation, research efforts were dedicated to the fabrication and characterization of nanocomposites in order to enhance the energy density at both room temperature and elevated temperature. The dielectric capacitors are fabricated using nanocomposites composed of BaTiO 3 nanoparticles with polyimide (PI) matrix aiming at combining the high relative dielectric permittivity of the ceramic filler and the high breakdown strength of the polymeric matrix. Dielectric energy storage performance is assessed for nanocomposites with volume fractions ranging from 0 to 20% under operating frequency from 20 Hz to 1 MHz and temperatures ranging from 20 to 120 ∘ C. It is observed that with the increase of temperature, the capacitance increased while the energy density slightly decreased but significantly higher than pure polymer samples. The highest energy density was found for BaTiO 3 /PI nanocomposites with 20% volume fraction, 9.63 J/cm 3 at 20 ∘ C and 6.79 J/cm 3 at 120 ∘ C. Overall, testing results indicate that using nanocomposites of BaTiO 3 /PI as a dielectric component shows promise for implementation to preserve high energy density values up to temperatures of 120 ∘ C.